PKM PENDAMPINGAN PRODUKSI TAHU BERBASIS TEKNOLOGI DAN MANAJEMEN KEUANGAN DI SENTRA INDUSTRI TAHU NGLONGSOR, TRENGGALEK - Purwati, Titik; Hindun, Nurmala (PAMBUDI, 2018)
Tofu is a nutrient-rich snack. Soy-based. One area that produces tofu is the Corah Mulyo, Nglongsor, Tugu, which is the Tofu Industry Center in Trenggalek Regency. As confectionary from simple and traditional industrial processed products, hygiene and waste disposal aspects are largely lacking in careful attention. Soybeans are ground into mush, boiled, filtered, quenched and dregs separated, the essence is boiled again, given liquid vinegar, clots, squeezed and printed. The remaining juice is a waste. The team of PKM P2M IKIP Budi Utomo Malang introduced the management of the production process that is efficient and free from waste and also provides an understanding of the financial governance of business results. With a different milling machine, soybeans are ground to produce essence and pulp. Boiled quintessence is given a liquid nautical juice, clots, squeezed and printed. The remaining juice can be used for making drinks, odorless and environmentally friendly. Methods and approaches through transformation and mentoring. End of activities, Team of PKM (1) Transform hygienic tofu production processes, (2) Ability to operate soybean grinding machines, (3) Socialize handling of production processes with sanitation and a clean work environment, (4) Understand the value of financial governance results business tofu.